An Application of Electron Energy Loss Spectroscopy to a Cycled Nickel Positive Electrode of a Nickel Metal Hydride Battery. (July 2021) - Carpenter, Graham J.C.; Couillard, Martin; Wronski, Zbigniew S.
Abstract : Abstract: Transmission electron microscopy (TEM) offers significant potential for studying chemical changes that occur in a battery electrode at a spatial resolution approaching atomic dimensions, provided a representative specimen can be prepared. The purpose of this paper is to show that it is possible to examine an electrode in the charged condition using TEM, while avoiding major changes in chemistry from specimen preparation. We also demonstrate the power of electron energy-loss spectroscopy (EELS) for phase identification at high spatial resolution. The origin of "fading" of an electrode after repeated charge-discharge cycling is also discussed.